Changes in extracellular space volume and geometry induced by cortical spreading depression in immature and adult rats - Mazel, T; Richter, F; Vargová, L; Syková, E (Physiological research, 2002)
Changes in extracellular space (ECS) diffusion parameters, DC potentials and extracellular potassium concentration were studied during single and repeated cortical spreading depressions (SD) in 13-15 (P13-15), 21 (P21) and 90-day-old (adult) Wistar rats. The real-time iontophoretic method using tetramethylammonium (TMA+)-selective microelectrodes was employed to measure three ECS parameters in the somatosensory cortex: the ECS volume fraction alpha (alpha = ECS volume/total tissue volume), ECS tortuosity lambda (increase in diffusion path length) and the nonspecific TMA+ uptake k'. SD was elicited by needle prick. SD was significantly longer at P13-15 than at P21 and in adults. During SD, alpha in all age groups decreased from 0.21-0.23 to 0.05-0.09; lambda increased from 1.55-1.65 to 1.95-2.07. Ten minutes after SD, alpha (in adults) and lambda (all age groups) increased compared to controls. This increase persisted even 1 hour after SD. When SD was repeated at 1 hour intervals, both alpha and lambda showed a gradual cumulative increase with SD repetition. Our study also shows that cortical SD is, as early as P13, accompanied by severe ECS shrinkage and increased diffusion path length (tortuosity) with values similar to adults, followed by a long-lasting increase in ECS volume and tortuosity when compared to pre-SD values.
Keywords: Potassium; Male; Aging; Rats, Wistar; draslík; Electrophysiology; mikroelektrody; Diffusion; Somatosensory Cortex; Cortical Spreading Depression; difuze; mužské pohlaví; potkani Wistar; osmolární koncentrace; kvartérní amoniové sloučeniny; krysa rodu Rattus; Animals; Quaternary Ammonium Compounds; elektrofyziologie; extracelulární prostor; Extracellular Space; zvířata; Osmolar Concentration; Rats; stárnutí; somatosenzorické korové centrum; šířící se kortikální deprese; Microelectrodes